Analisis Dampak Efisiensi Anggaran Terhadap Kesejahteraan Tenaga Honorer di SMA 1 Remboken Kabupaten Minahasa Provinsi Sulawesi Utara - Yescina Gabriela Tambunan; Apeles Lexi Lonto; Julien Biringan (CV. Kurnia Grup, 2026)
This study explores the impact of budget efficiency policies on the welfare of honorary staff at SMA Negeri 1 Remboken, Minahasa Regency, North Sulawesi Province. Budget efficiency policies aim to increase the effectiveness of public funds, but can impact the management of non-ASN staff in the education sector. This study uses a qualitative approach with descriptive-analytical methods to deeply understand the experiences and perceptions of honorary staff and school principals regarding the implementation of these policies. The research subjects consisted of honorary teachers, administrative staff, and principals who were selected purposively. Data collection was conducted through semi-structured interviews, observation, and documentation studies, while data analysis followed the interactive model of Miles, Huberman, and Saldana (1994) which includes reduction, presentation, and drawing conclusions. The results show that budget efficiency policies affect the distribution and management of school funds, resulting in limited honorariums, minimal welfare benefits, and uncertainty about the employment status of honorary staff. This condition creates an imbalance between the contribution of honorary staff to learning activities and school operations and the level of welfare they receive. These findings provide input for the development of public policies in the field of education, improving school budget management, and protecting and improving the welfare of honorary staff.